The Relationship of Education Level and Economic Status with The Use of Scraping on The Elderly Based on Transcultural Nursing - Ikha Ardianti; Errix Kristian Julianto (Universitas Nahdlatul Ulama Surabaya, 2022)
Complementary nursing and alternative medicine have been widely used by the community, one of which is scrapings. Scrapings are believed to be effective in curing symptoms of unwell in the elderly because the method is easy. It also does not require a lot of money. However, the impact of using scrapings that are carried out continuously will cause an addiction effect. Efforts to improve the health status of the elderly can be influenced by various factors, including cultural and social culture. This study aims to determine the relationship between education level and economic status with the use of scrapings on the elderly. This study employed a correlation design with a retrospective approach and observational analysis with quantitative methods. The population in this study were all the elderly in the village of Prambon Tergayang, Soko District, Tuban Regency, as many as 68 people. The sample in this study was 42 elderly who were willing to become respondents. The result showed a relationship between educational factors and the use of scrapings by the elderly. The Spearman Rho statistical test showed the p-value = 0.007. There was no relationship between economic factors and the use of scrapings by the elderly (p-value = 0.071). Research examining the effect of scrapings on the health of the elderly can be focused on as a topic for future research.